Growth Of Three Tobacco Varieties (Nicotiana Tabacum L) Seedlings Using Biochar Media On Clay-Structured Soil - Ramlayani, Ramlayani; Rahim, Iradhatullah; Qadri, Sri Nur; Sukmawati, Sukmawati; Zamzam, Syamsiar (Urecol Journal. Part D: Applied Sciences, 2025)
This study aims to evaluate the effect of biochar-based growing media on the growth of seedlings of three tobacco (Nicotiana tabacum L.) varieties—Jinten, Paiton-2, and Perancak-95—cultivated in clay-textured soil. Clay soil poses challenges for plant growth due to poor drainage and limited aeration, which can hinder root development and nutrient absorption. To address these limitations, biochar is used as a soil amendment, known to improve soil structure, enhance water retention, and increase nutrient availability. The experiment was arranged in a factorial Randomized Complete Block Design (RCBD) with two factors: tobacco varieties and seed soaking treatments (warm water, warm water with Azotobacter, and warm water with biohumic), each replicated three times. Observed parameters included plant height, leaf dimensions, stem diameter, root length and weight, and total fresh biomass. The results are expected to identify the tobacco variety that responds best to biochar treatment and provide recommendations for optimal seedling growth in marginal soils.